2016
DOI: 10.1111/1744-7917.12359
|View full text |Cite
|
Sign up to set email alerts
|

Between fighting and tolerance: reproductive biology of wingless males in the ant Cardiocondyla venustula

Abstract: Male reproductive tactics vary widely across the species of the ant genus Cardiocondyla, from obligatory lethal combat among co-occurring males to complete mutual tolerance. The African species C. venustula Wheeler, 1908 has an intermediate phylogenetic position between taxa with fighting males and taxa with tolerant males and also shows an intermediate male behavior. Males from 2 native populations in South Africa and a population introduced to Puerto Rico attacked and killed freshly eclosing rivals but rarel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
(66 reference statements)
0
5
1
Order By: Relevance
“…Field studies gave conflicting results concerning queen number: while Wheeler [24] reported on regular singlequeening in an introduced population in Puerto Rico, our own observations revealed the regular presence of multiple queens per colony both in introduced and native populations [23,25]. The finding of dense populations of C. venustula near Pretoria and Bergville, South Africa, allowed us to conduct detailed analyses of the genetic structure of colonies and populations and how they are influenced by male territoriality and female dispersal on foot.…”
Section: Introductioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Field studies gave conflicting results concerning queen number: while Wheeler [24] reported on regular singlequeening in an introduced population in Puerto Rico, our own observations revealed the regular presence of multiple queens per colony both in introduced and native populations [23,25]. The finding of dense populations of C. venustula near Pretoria and Bergville, South Africa, allowed us to conduct detailed analyses of the genetic structure of colonies and populations and how they are influenced by male territoriality and female dispersal on foot.…”
Section: Introductioncontrasting
confidence: 58%
“…Winged queens have regularly been observed to disperse on foot, and some of them may enter and mate in alien nests, similar to what has been observed in Palearctic Cardiocondyla [30,44]. Wingless males of C. venustula may therefore not only compete for mating with their sisters [22,23] but also for mating with alien queens. The presence of multiple fertile queens in field and also lab colonies (unpublished data) suggests that C. venustula is facultatively polygynous, in contrast to the obligatorily monogynous Palearctic clade.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Fighting is costly in terms of energy use, time, injury risk, increased risk of predation, and may even result in death (Kelly & Godin, 2001; Briffa & Elwood, 2004; Arnott & Elwood, 2009). Selection should favor accurate gathering of information to enable tactical decision‐making (Parker, 1974; Arnott & Elwood, 2008; Jacobs & Heinze, 2017). Some traits, including both static traits (such as body size) and dynamic traits (such as behavior) may function as an indicator of fighting ability, and honest signaling may reliably convey the condition or status of individuals (Hill, 1991; Eldred et al ., 2016; Yasuda & Koga, 2016; Alvarez et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%